Effect of Gamma Irradiation on the Nutritional Quality of Maize Cultivars (Zea mays) and Sorghum (Sorghum bicolor) Grains - Mohamed, A.H. Rushdi; Mohamed, M. Eltayeb; Gammaa, A.M. Osman; Diab, E.E.; Amro, B. Hassan (Pakistan Journal of Nutrition, 2009)
To investigate the effect of gamma irradiation on the nutritional quality of maize and sorghum grains, packs were exposed to doses of 0 and 2 kGy in a 60 Co package irradiator. Irradiated and non-irradiated samples were stored at refrigeration temperatures. Proximate composition, minerals content, minerals bio-availability, tannins content, phytic acid content, protein fractions and in vitro protein digestibility were evaluated. The results indicated that gamma irradiation caused no effect on proximate composition, minerals content and minerals bioavailability. For protein fractions, in both maize cultivars no significant differences were observed in all fractions, except in prolamins and glutelins of Maize 75. While for sorghum significant increase in globulins, prolamins and glutelins was observed. While, gamma irradiation reduced the phytic acid and tannins contents significantly. The in vitro protein digestibility of maize cultivars was increased significantly, while the digestibility of sorghum was reduced.